Procesni vidiki zastaranja - Zobec, Jan (Pravni letopis, 2015)
Although the institute of statutory time limitation belongs to substantive private law, it reveals some conspicuous procedural effects, which find expression at two levels. The first is intrinsic, inherent in the very essence of this phenomenon, and is revealed mostly by the jurisprudence of the ECtHR, the CC and also by the CJEU. It is all about the effect of time period limitations on the right of access to the court, which includes also the right to a decision on the merits. Although such a decision (dismissing the claim for the failure to comply with the prescribed time limits) formally counts as a "substantive" one, it is actually a bare mechanical decision. The second level of the procedural aspects of time limitation represents the external contact of this institute with civil proceedings. It concerns less doctrinal yet more practical questions. This article is structured upon the two levels: the first part presents procedural components of the topic, giving a brief analysis of the jurisprudence of the ECtHR, CC and CJEU, while the second part discuses some outstanding questions about the procedural life of the time limitation.
Keywords: civilno procesno pravo; tožbe; zastaranje